Economics of infrastructure: growth and development - Dash, L.N. (ed.) (New Delhi, 2007)
Infrastructure is the foundation for development of any country. Recognising their importance in economic development and for the society as a whole, these services are also referred to as "Social Overheads'. Yet for millions in many poor countries, these services are still beyond reach. The development community and the developing countries recognize the key role that infrastructure pays, both directly and indirectly. The myriad kinds of issues/problems confronting the infrastructure sector assume paramount importance now because the high growth rate exerts pressure on this sector. If infrastructure growth fails to keep pace, it will cripple economic growth. It has, therefore, been felt necessary to take up the work to sharpen the various aspects of infrastructure sector which may be of some use to planners and policy-makers.
Keywords: Economic Development